Social, Economic and Environmental Sustainability as Perceived by Inhabitants: A Mixed Method Study of Impact Assessment - Suvarna, Vaishali Y.; Rodrigues, Lewlyn L.R.; Rao, Potti Srinivasa; Ravindranatha,; Nair, Girish (Journal of Sustainability and Environmental Management, 2022)
Sustainability is the buzzword in the national agenda of almost all the countries, specifically in terms of its three dimensions. The purpose of this research was to investigate the sustainability aspects of Udupi Power Corporation Limited (UPCL), which is a 2x600 MW imported coal-based thermal power plant, situated in a village in Karnataka State of India. The social, economic and environmental impact of UPCL on the surrounding villages as perceived by its inhabitants on the sustainable growth of the power plant has been studied based on mixed methods approach. The research is a longitudinal study and follows an explanatory sequential design, based on questionnaire survey and in-depth interviews of inhabitants of the villages surrounding the Thermal Power Plant (TPP), employees of the TPP, and other stakeholders. The results have clearly identified the measures the TPP authorities have taken to ensure the sustainable growth and the Corporate Social Responsibilities (CSR) exhibited by the plant. DOI: https://doi.org/10.5281/zenodo.6198262